Clinical Judgement in ICU Nurse: A Concept Analysis - Aryani, Denissa Faradita; Rustina, Yeni; Nurachmah, Elly; Dahlia, Debie; Gupta, Prateek; Apriyanti, Efa (Universitas Aisyah Pringsewu, 2024)
Clinical judgment is a critical and multifaceted process essential for ICU nurses, integrating technical expertise and interpersonal skills to ensure safe, effective patient care. Clinical judgment, recognized as a core competency in intensive care nursing, requires further conceptual clarity. This study aimed to define and analyze the concept of clinical judgment in ICU nurses using Walker and Avant’s eight-step concept analysis method. A comprehensive literature search was conducted across databases including CINAHL, Medline, Scopus, ProQuest, SpringerLink, ClinicalKey Nursing, EMBASE, ScienceDirect, EBSCOhost, and Google Scholar, covering publications from 1994 to 2024. The analysis identified key attributes of clinical judgment: clinical knowledge, critical thinking, practical wisdom, data prioritization, intuition, scientific analysis, evidence use, and interaction. Antecedents included education, knowledge, experience, analytical ability, and the nursing process. Consequences of clinical judgment were accurate responses, reflective practice, safe nursing care, and improved patient safety. Decision-making was identified as the primary empirical referent. This concept analysis demonstrates that clinical judgment in ICU nurses is developed through a synthesis of critical thinking, clinical expertise, and situational experience, reinforcing its significance in the delivery of high-quality critical care.